MHC Class I Cross-Presentation by Dendritic Cells Counteracts Viral Immune Evasion - Nopora, Katrin; Bernhard, Caroline A.; Ried, Christine; Castello, Alejandro A.; Murphy, Kenneth M.; Marconi, Peggy; Koszinowski, Ulrich H.; Brocker, Thomas (Frontiers in Immunology, 2012)
DCs very potently activate CD8+ T cells specific for viral peptides bound to MHC class I molecules. However, many viruses have evolved immune evasion mechanisms, which inactivate infected DCs and might reduce priming of T cells. Then MHC class I cross-presentation of exogenous viral Ag by non-infected DCs may become crucial to assure CD8+ T cell responses. Although many vital functions of infected DCs are inhibited in vitro by many different viruses, the contributions of cross-presentation to T cell immunity when confronted with viral immune inactivation in vivo has not been demonstrated up to now, and remains controversial. Here we show that priming of Herpes Simplex Virus (HSV)-, but not murine cytomegalovirus (mCMV)-specific CD8+ T cells was severely reduced in mice with a DC-specific cross-presentation deficiency. In contrast, while CD8+ T cell responses to mutant HSV, which lacks crucial inhibitory genes, also depended on CD8+ DCs, they were independent of cross-presentation. Therefore HSV-specific CTL-responses entirely depend on the CD8+ DC-subset, which present via direct or cross-presentation mechanisms depending on the immune-evasion equipment of virus. Our data establish the contribution of cross-presentation to counteract viral immune evasion mechanisms in some, but not all viruses.